2022
DOI: 10.1093/plphys/kiac311
|View full text |Cite
|
Sign up to set email alerts
|

A calmodulin-like protein (CML10) interacts with cytosolic enzymes GSTU8 and FBA6 to regulate cold tolerance

Abstract: Calmodulin-like proteins (CMLs) are Ca2+ sensors involved in plant growth and development as well as adaptation to environmental stresses; however, their roles in plant responses to cold are not well understood. To reveal the role of MsCML10 from alfalfa (Medicago sativa) in regulating cold tolerance, we examined transgenic alfalfa and Medicago truncatula overexpressing MsCML10, MsCML10-RNAi alfalfa, and a M. truncatula cml10-1 mutant and identified MsCML10-interacting proteins. MsCML10 and MtCML10 transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…MtCML42 positively regulates cold tolerance through regulating MtCBF1 and MtCBF4 expression, and regulates flowering time through sequentially downregulation of MtABI5 and upregulation of MtFTa1 (Sun et al, 2021). Alfalfa (Medicago sativa) MsCML10 regulates cold tolerance through activating MsGSTU8 and MsFBA6, leading to improved maintenance of ROS homeostasis and increased accumulation of sugars for osmoregulation, respectively (Yu et al, 2022). MsCML46 enhances tolerance to abiotic stresses through alleviating osmotic stress and oxidative damage in transgenic tobacco (Du et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…MtCML42 positively regulates cold tolerance through regulating MtCBF1 and MtCBF4 expression, and regulates flowering time through sequentially downregulation of MtABI5 and upregulation of MtFTa1 (Sun et al, 2021). Alfalfa (Medicago sativa) MsCML10 regulates cold tolerance through activating MsGSTU8 and MsFBA6, leading to improved maintenance of ROS homeostasis and increased accumulation of sugars for osmoregulation, respectively (Yu et al, 2022). MsCML46 enhances tolerance to abiotic stresses through alleviating osmotic stress and oxidative damage in transgenic tobacco (Du et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study suggested that M. sativa MsFBA6 interacts with CaM-like 10 protein, MsCML10 (8). To determine whether this property is conserved with the Arabidopsis orthologs, we used in planta split-luciferase (SL) assays to test the interaction between AtFBA4 and AtCML11, the closest respective Arabidopsis orthologs of MsFBA6 and MsCML10.…”
Section: Resultsmentioning
confidence: 99%
“…A study using Medicago sativa and Medicago truncatula highlighted the increased freezing resistance that resulted from elevated FBA gluconeogenic activity under cold stress (8). This phenomenon was reported to be a consequence of the interaction of M. sativa calmodulin-like 10 (MsCML10) with MsFBA6, leading to enhanced gluconeogenesis and the accumulation of sugars as osmoprotectants (8).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations